Adolescents perception of paternal figures' involvement in their sexuality education - Siboyana, Bafana (My University, 2008)
The main aim of the study was to investigate adolescents’ perceptions of the paternal/father figures’ involvement in their sexuality education. Other aims included to determine adolescents’ perception of paternal/father figures’ knowledge of sexuality education; aspects/topics that are discussed; and the gender differences in paternal figures’ involvement with adolescents’ sexuality education. The study sample consisted of 67 adolescents aged between 13-19 years and was chosen through purposive, non-probability sampling technique from Illinge Secondary School at Vosloorus Township, Ekurhuleni Metropolitan Council. A questionnaire designed by the researcher was used to collect the data for the study. The results of the present study indicated that a small number of the adolescents perceive their paternal/father figures as involved in the discussion of sexuality matters. Nevertheless a highest number of the participants in the study perceive a paternal figure as a right source of sexuality education. However, the study shows that participants perceive their paternal figures as authoritarian and having poor communication about sexuality matters. This study indicated that there is no trend in adolescents’ perceptions of their paternal figures’ adequacy and inadequacy of knowledge regarding competency/incompetence in discussing sexuality topics. The main topic that the participants indicated to be receiving paternal figures’ attention is adolescents’ pregnancy and parenting. However, there is an indication that sexual intercourse is not mentioned as the antecedent to pregnancy. A large number of adolescents in this study indicated that there is a presence of a significant gender difference in the sexuality education. An increased father forum as well as involvement of social institutions and the professional and community based work force is recommended to address the need for father/paternal figures’ involvement in the sexuality education of adolescents.
Keywords: sexuality education; adolescents; perception